(untitled) (Daffodil International University Journal of Science and Technology, 2010)
A research had been taken to find out the suitability of blended curtain in respect to the property of 100% similar cotton curtain. Here, two main factors viz. wt. and strength are taken in to account considering the effect of washing on it. From the test results, it is shown that 50:50/ jute: cotton blended curtain is comparable to the 100% cotton curtain of Tk. 90 /meter. Even better than the properties of 100% cotton curtain of Tk. 60/ meter. Keywords: Jute, Cotton, Washing, Strength, Blended, Mechanical, Weight, Curtain. DOI: 10.3329/diujst.v5i1.4373 Daffodil International University Journal of Science and Technology Vol.5(1) 2010 pp.1-5